Virtual laboratory of protists: Learning media to enhance scientific attitudes - Ardina Dwi Yani Inayah; Rizhal Hendi Ristanto; Diana Vivanti Sigit; Mieke Miarsyah (JPBIO (Jurnal Pendidikan Biologi), 2020)
A scientific attitude is important for students to have because scientific attitudes affect the learning process and outcomes. One way to improve scientific attitudes in students is using interactive and interesting learning media. Therefore, this study aims to see the effect of using virtual laboratory media on students’s scientific attitudes. The method used in this study is a quantitative method with a quasi-experimental design. The instrument used in this study was a scientific attitude questionnaire in the form of a Likert scale. The data were analyzed descriptively and differently. The research samples used was 70 samples divided into 35 samples in the experimental class and 35 samples in the control class. Based on the results of the study, it was seen that there was an increase in the average value of scientific attitudes in each dimension of scientific attitudes after carrying out learning with virtual laboratory media. It was also known that based on ANCOVA test, the significance value was 0.000<0.05. So, it can be concluded that virtual laboratory media can improve the scientific attitude of students. Keywords: Biology learning, laboratories, protist, scientific attitudes